A repairable connection for earthquake‐resisting moment frames. Issue 3 (9th August 2019) - Richards, Paul
Abstract: Nominated for the Bernt Johansson Outstanding Paper Awards at Nordic Steel 2019 Most steel moment frames are designed so that the beams act as structural fuses during earthquake loading. This approach, while good for saving lives, has poor resilience because it is difficult to replace damaged beams in a building. A repairable steel moment‐frame connection has been developed that may be attractive to engineers and building contractors. The connection has a fuse plate bolted to the beam bottom flange which experiences shear yielding during severe earthquakes, protecting both the column and the beam. After an earthquake, the fuse plates can be removed and replaced to unlock residual frame deformations and prepare the building for another event. Full‐scale experiments were conducted to validate the performance of this repairable connection. Two tests were performed with a W690 #αμπ##ξ000Δ7; 125 beam and W530 #αμπ##ξ000Δ7; 196 column. The tests demonstrated rotation capacities of at least 0.05 rad, which exceeds AISC requirements for special moment frames. The fuse plate was effective in preventing beam damage in each test, and the second test demonstrated that the connection could be repaired by replacing the fuse plate.